An LC-MS/MS method to determine PABA and DIP. Issue 5 (11th January 2016) - Yin, Lei; Yang, Junfeng; Meng, Xiangjun; Yang, Bo; Su, Chong; Yang, Zhichao; Zheng, Mi; Zhao, Limei; Gu, Jingkai; Xin, Guijie
Abstract : A liquid chromatography-tandem mass spectrometric method using electrospray ionization for the simultaneous quantitation of p -acetaminobenzoic acid and N, N -dimethylamino-2-propanol in human plasma. Abstract : A liquid chromatography-tandem mass spectrometric (LC-MS/MS) method using positive/negative electrospray ionization (ESI) switching for the simultaneous quantitation of p -acetaminobenzoic acid (PABA) and N, N -dimethylamino-2-propanol (DIP) in human plasma has been developed and validated. After simple protein precipitation using acetonitrile, the analytes and internal standard (IS) diazepam were separated on a CAPCELL PAK Phenyl column (150 × 2.0 mm, 5 μm) using formic acid : water (1 : 1000, v/v) as solvent A and acetonitrile as solvent B at a flow rate of 0.4 mL min −1 . N, N -Dimethylamino-2-propanol and the IS were detected by positive ion electrospray ionization followed by multiple reaction monitoring (MRM) of the transition at m / z 104.0 → 86.1 and 256.3 → 167.1, respectively. p -Acetaminobenzoic acid was detected by negative ion electrospray ionization followed by MRM of the transitions at m / z 178.1 → 134.0. The method was linear for PABA and DIP in the concentration range of 0.02–10 μg mL −1 with intra- and inter-day precisions (as relative standard deviation) of ≤5.81% and accuracy (as relative error) of ≤6.52% and the limit of detection (LOD) values were 10 and 5 ng mL −1, respectively. The method was successfully applied to a pharmacokinetic study of the analytes in humans after oral administration of 1.0 g inosiplex tablets.